AKSI BESAR DADA (BEBAS SAYURAN DARI PESTISIDA) PADA PENINGKATAN PERILAKU MASYARAKAT TENTANG DAMPAK PESTISIDA PADA SAYURAN SEGAR - Hidayah, Nurul (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2025)
The excessive use of pesticides on fresh vegetables can have adverse effects on both human health and the environment. The lack of public awareness regarding the content and risks of pesticide residues is a serious concern, particularly in agricultural areas such as Sumberngepoh Village, Lawang District. This community service activity aimed to empower health cadres through educational outreach focused on improving knowledge and influencing community behavior in selecting and processing fresh vegetables safely. The activity was conducted on May 25, 2024, involving 15 health cadres as key participants. The methods used included educational lectures, interactive discussions, and simulation of community-based counseling. The results indicated an increased understanding among participants regarding types of pesticides, their potential health hazards, and preventive measures through proper washing and vegetable selection. The cadres also expressed their readiness to disseminate the information to the wider community. This activity is expected to be a starting point for promoting healthier vegetable consumption patterns and encouraging active participation of health cadres in environmental health promotion.